2008
DOI: 10.1093/toxsci/kfn166
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Mouse and Human Peroxisome Proliferator−Activated Receptor Alpha by Perfluoroalkyl Acids of Different Functional Groups and Chain Lengths

Abstract: Perfluoroalkyl acids (PFAAs) are surfactants used in consumer products and persist in the environment. Some PFAAs elicit adverse effects on rodent development and survival. PFAAs can activate peroxisome proliferator-activated receptor alpha (PPARalpha) and may act via PPARalpha to produce some of their effects. This study evaluated the ability of numerous PFAAs to induce mouse and human PPARalpha activity in a transiently transfected COS-1 cell assay. COS-1 cells were transfected with either a mouse or human P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
182
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(209 citation statements)
references
References 57 publications
21
182
1
2
Order By: Relevance
“…The human PPARα is more sensitive to C6A than C8S as reported by Wolf et al (2008), where concentrations predicted to produce 20% of the overall maximal responses for C6A and C8S are 16 and 262 μM, respectively. Nakamura et al (2016) reported that C6A as well as C8A induced DNA damage in an alkaline comet assay, using TK +/-heterozygote of the TK6 human lymphoblastoid cell line.…”
Section: Comparison To Human Datamentioning
confidence: 62%
“…The human PPARα is more sensitive to C6A than C8S as reported by Wolf et al (2008), where concentrations predicted to produce 20% of the overall maximal responses for C6A and C8S are 16 and 262 μM, respectively. Nakamura et al (2016) reported that C6A as well as C8A induced DNA damage in an alkaline comet assay, using TK +/-heterozygote of the TK6 human lymphoblastoid cell line.…”
Section: Comparison To Human Datamentioning
confidence: 62%
“…6 carbon) PFAS have a longer half-life and are more potent activators of the peroxisome proliferator-activated receptor (PPAR)-a pathway (Buck et al 2011). There was also a positive correlation between carbon chain length and hepatomegaly (Kudo et al 2006), total and renal clearance (Kudo et al 2001;Ohmori et al 2003), hydrophobicity (Goecke-Flora and Reo 1996), and induction of PPARa (Wolf, Takacs, et al 2008), peroxisomal fatty acyl CoA-oxidase, hepatic phosphocholine (Goecke-Flora and Reo 1996), and peroxisomal b-oxidation (Kudo et al 2006). Following a systematic review of the literature on the immune effects of PFOA and PFOS, the National Toxicology Program Office of Health Assessment and Translation (OHAT) concluded that there was a moderate level of evidence that PFOA and PFOS suppress the anti-vaccine antibody response, and are presumed to be an immune hazard to humans (OHAT 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their structural similarity to fatty acids, previous mechanistic studies focused on PFCs' toxicity carried out through the peroxisome proliferator-activated receptor (PPAR) pathway (Wolf et al 2008). Direct binding and activation to PPARs have been demonstrated (Wolf et al 2012;Takacs and Abbott 2007).…”
Section: Introductionmentioning
confidence: 99%